P10 Is pseudomonas eradication beneficial in non-CF bronchiectasis? an eight year retrospective cohort review. (December 2018) - Casey, HR; Millington, K; Easton, F; Malin, A
Abstract : Introduction: We report on Pseudomonas eradication within our non-CF bronchiectasis service based at a large district general hospital covering a population of 5 00 000. Following the BTS 2010 guidelines included in our protocol is that all non-CF bronchiectasis patients have 3 monthly sputum cultures monitoring for Pseudomonas. Those with repeated Pseudomonas culture are offered eradication. We carried out a retrospective review of our cohort data to evaluate successful Pseudomonas eradication and whether this had a beneficial impact on clinical or physiological parameters. Methods: Database-driven, electronic patient records from the bronchiectasis service were analysed. Baseline patient and Pseudomonas infection data were collected. Repeat Pseudomonas culture was required to indicate colonisation. The colonised group were offered eradication and outcomes were recorded within our dedicated web-based database. Data included: time point, duration of colonisation, drugs used, successful eradiation and for how long if re-colonised, FEV1% change, MRC breathlessness score and exacerbation frequency post-eradication. Results: 288 patient clinical records were analysed. 48 were excluded as deemed not to have bronchiectasis leaving a cohort of 240 non-CF bronchiectasis patients. Of these, 148/240 (62%) had at least one positive Pseudomonas culture with 107/240 (45%) showing colonisation. Of those with colonisation, 77/107 (72%) underwent eradication (see table 1). 51 tolerated the treatment course. 18 did not complete due to side effects or intolerance (no data for 8 patients). Immediate eradication was achieved in 49%. However, only 24% were able to achieve long term eradication (sputum negative for >6 months). We were not able to demonstrate an improvement in FEV1%, MRC grade or exacerbation rate in the year after eradication. Conclusion: We believe this is the largest single cohort describing Pseudomonas eradication outcomes. Most combinations of anti- Pseudomonas antibiotics achieved eradication in around half those treated, but this was maintained for only a quarter of patients. There were no clear markers to indicate if eradication was going to be successful, including prior duration of colonisation. We were unable to indicate definite clinical benefits from eradication. Given that the current guideline suggests eradication, a prospective randomised trial is needed to answer whether this is beneficial.